2011
DOI: 10.3168/jds.2010-3562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ensiling time and inoculation on alteration of the starch-protein matrix in high-moisture corn

Abstract: The fates of hydrophobic zein proteins, which encapsulate corn starch to create vitreous endosperm, have not been investigated in high-moisture corn (HMC). To assess influences of ensiling time and inoculation on zein proteins in HMC, quadruplicate samples of 2 random corn hybrids (A and B), containing 25.7 and 29.3% moisture, were ground, inoculated with (I) or without 600,000 cfu/g of Lactobacillus buchneri 40788 (Lallemand Animal Nutrition, Milwaukee, WI), and ensiled for 0, 15, 30, 60, 120, and 240 d. Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
185
2
27

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(245 citation statements)
references
References 24 publications
25
185
2
27
Order By: Relevance
“…The effect of the ensiling time on starch degradability and protein integrity of the endosperm matrix was previously described for silage of grains harvested with high-moisture corn (HOFFMAN et al, 2011). However, as far as we know, no studies reported the effect of longer ensiling periods on the composition and degradability of corn with medium vitreousness and high levels of DM.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The effect of the ensiling time on starch degradability and protein integrity of the endosperm matrix was previously described for silage of grains harvested with high-moisture corn (HOFFMAN et al, 2011). However, as far as we know, no studies reported the effect of longer ensiling periods on the composition and degradability of corn with medium vitreousness and high levels of DM.…”
Section: Introductionmentioning
confidence: 88%
“…Increases in corn grain starch and DM digestibility evaluated by in vitro and in situ assays, respectively, were reported after increasing the storage period of the entire crop, high-moisture corn grain and hydrated corn grain silages (BENTON et al, 2005;DER BEDROSIAN et al, 2012). The effect of ensiling time on silage degradability is probably due to the degradation and/or solubilization of zein subunits over the ensiling period (LAWTON, 2002;HOFFMAN et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En tal sentido, se hace apremiante la búsqueda de soluciones y alternativas que logren dar respuesta a las necesidades básicas en la producción animal (Hoffman et al, 2011). Un método económico y de fácil acceso es el ensilaje, el cual permite conservar productos de rápido deterioro.…”
Section: Introductionunclassified
“…Asimismo, Miranda et al (2014) reportaron extender el tiempo de conservación sin afectar al contenido nutritivo y con reducción de las partes fibrosas de la yuca al inocular cultivo mixto de bacterias ácido lácticas y levaduras. De igual manera, Hoffman et al (2011), Dadvar et al (2013) y Lyncha et al (2014, con el uso de un cultivo mixto se lograron controlar el crecimiento de microorganismos toxigénicos como clostridium, S. aureus, C. botulinum, Salmonella sp. y Listeria monocytogenes, así como de los microorganismos asociados al deterioro directo del alimento.…”
Section: Introductionunclassified